Study for risks of amniocentesis in anterior placenta compared to placenta of other locations - Minako Goto; Masamitsu Nakamura; Hiroko Takita; Akihiko Sekizawa (Elsevier, 2021)
Objective: This study aimed to compare the risks of amniocentesis between anteriorly located placentas and placentas in other locations and assess the factors that cause procedure-related complications. Materials and methods: We prospectively studied women with singleton pregnancies who underwent amniocentesis between 2014 and 2020. The amniocentesis puncture sites were determined using ultrasonography. Women were classified into two groups according to their placental location. Medical records were retrospectively reviewed and characteristics and complications were compared between the groups of patients with different placental locations. Results: During the study period, 629 women underwent amniocentesis. Three cases (0.5%) of premature rupture of membranes and one case (0.3%) of fetal loss within four weeks of amniocentesis were found. Puncture failure was observed in 14 cases (2.2%). Puncture failure included procedures with failure to obtain an adequate sample and procedures requiring more than three needle insertions. There was no significant difference in the frequency of puncture failure between the two groups. Logistic regression analysis revealed that uterine myoma (odds ratio [OR] 11.92; 95% CI, 3.04-45.17) and tenting membrane (OR 33.57; 95% CI, 6.45-178.41) were associated with puncture failure. Conclusion: Anteriorly located placenta is not a risk factor for amniocentesis-related adverse outcomes. Instead, puncture failure frequently occurs in case of uterine myoma and tenting membrane. If puncture failure occurs, or if the puncture is difficult to perform, then the procedure should be considered technically difficult and postponed until it can be more easily performed.